(untitled) (INTERNATIONAL JOURNAL OF APPLIED SCIENCE & TECHNOLOGY, 2020)
Traditional Knowledge of the earth is based on thousands of years’ experience. It is developed and preserved by local and endogenous communities for centuries as a strategy for their survival in the biosphere. Traditional Knowledge (TK) is essentially culturally oriented or culturally based, and it is integral to the cultural identity of the social group in which it operates and is preserved. Traditional Knowledge is an open ended way to refer to tradition based literary, artistic or scientific works, perform ones, inventions scientific discoveries, designs; marks names and symbols, undisclosed information and all other tradition on based innovations and creations resulting from intellectual activity. The definition of Traditional Knowledge use by the World Intellectual Property Office (WIPO) includes indigenous knowledge relating to categories such as agricultural knowledge medicinal knowledge, biodiversity related knowledge and expression of folklore in the form of music, dance, song, handicraft designs stories and artwork.